Seeing Roman life through water: Exploring Pompeii’s public baths via carbonate deposits - Gül Sürmelihindi; Cees Passchier; Monika Trümper; Thomas Heide; Christoph Spötl; Denis Scholz; Michael Weber; Friedrich Hawemann (Proceedings of the National Academy of Sciences, 2026)
The ancient city of Pompeii, destroyed by the eruption of Mt. Vesuvius in AD 79, shows technological improvements to its water supply after becoming a Roman colony. Its inhabitants relied on wells for their water supply prior to the installation of a Roman aqueduct. Carbonate incrustations deposited in various components of the city’s hydraulic infrastructure, including the aqueduct, its water towers, the well shafts, and pools of the public baths. The stable isotope and trace element composition of these carbonates differ markedly between structures supplied by wells and those fed by the aqueduct, reflecting the contrasting origins of their source waters. While the aqueduct was fed by karst springs, the wells tapped into highly mineralized groundwater from volcanic deposits. These geochemical distinctions allow for a detailed reconstruction of Pompeii’s water management system, particularly the transition from well- to aqueduct-based water supply. The periodicity of δ 13 C variations in carbonate crusts sampled from well, pools, and drainage channels of the Republican Baths offers insights into the operation and maintenance of the facility. δ 13 C values show a sharp drop from wells to bathing pools, suggesting contamination by human waste and implying that the bath water was not regularly replenished in the Republican Baths.